The i-EUS consensus on the management of pancreatic fluid collections – Part 1 - Capurso, Gabriele; Rizzo, Giacomo Emanuele Maria; Coluccio, Chiara; Crinò, Stefano Francesco; Cucchetti, Alessandro; Facciorusso, Antonio; Hassan, Cesare; Amato, Arnaldo; Auriemma, Francesco; Bertani, Helga; Binda, Cecilia; Cipolletta, Fabio; et al. (Digestive and liver disease, 2024)
Pancreatic fluid collections (PFCs), including pancreatic pseudocysts (PPs) and walled-off pancreatic necrosis (WON), are common complications of pancreatitis and pancreatic surgery. Historically, the treatment of these conditions has relied on surgical and radiological approaches; however, it has later shifted toward an endoscopy-based approach. With the development of dedicated lumen-apposing metal stents (LAMS), interventional Endoscopic Ultrasound (EUS)-guided procedures have become the standard approach for PFC drainage. However, there is still limited consensus on several aspects of the multidisciplinary management of PFCs. The interventional endoscopy and ultrasound (i-EUS) group is an Italian network of clinicians and scientists with special interest in biliopancreatic interventional endoscopy, especially interventional EUS. This manuscript describes the first part of the results of a consensus conference organized by i-EUS with the aim of providing evidence-based guidance on aspects such as indications for treating PFCs, the timing of intervention, and different technical strategies for managing patients with PFCs.